Trade-offs between forage yields and feed quality of Lablab purpureus, and milk yields in relation to planting and harvesting schedules - Agyemang, K.; Okike, Iheanacho; Makun, H.J.; Magaji, S.O. (Cambridge University Press, 2000)
This study, designed to investigate trade-offs between forage yields, feed quality and labour use in fitting a newly introduced crop, Lablab purpureus, into an existing farming system, adopted distinct applied and adaptive research approaches. The applied research component compared forage yields, nutrient contents and feeding qualities of L. purpureus harvested at 100, 114, 128 or 142 d after planting in an on-farm trial. The adaptive research investigated how farmers incorporated L. purpureus cultivation into their farming calendars given the constraints of labour for planting and harvesting. Harvested dry matter yields from the on-farm experiment were 1.28, 1.98, 1.74 and 1.44 t ha-1. The resultant hays were fed to four groups each of five Bunaji lactating cows in an on-farm feeding trial over a 10-week period. Ranking the various harvests for yield, the hays for feed value, animal responses to the feed consumed and the quality of animal products on a linear scale (1 to 4) to estimate a composite utility index, showed that harvesting at 114 d after planting gave the most desirable overall benefits. The survey for adaptive research showed bimodal rainfed and irrigated cultivation patterns for L. purpureus. Peaks were observed in September (31 percent of farmers) and November (24 percent) for planting, and in December (39.4 percent) and March (15 percent) for harvesting. Forage yields were, however, highest for the 3 percent of farmers who afforded labour to plant in July and harvest in October. The lack of congruence between highest forage yield periods and the peaks of cultivation of L. purpureus by farmers in the study area was mostly explained by very significant differences in the cost of hired and household labour in different months. Thus, socio-economic and cultural factors, including stakeholders; participation, need to be considered along with applied research results when recommending forage species for farmers' adoption.